Exploring selected antecedents of consumer–brand identification: The nature of consumer's interactions with product brands. Issue 4 (2nd July 2018) - Tuškej, Urška; Podnar, Klement
Abstract : Purpose: The purpose of this paper is to examine how brand anthropomorphism (BA), consumer–brand engagement (CBE), consumer skepticism and brand prestige influence consumer–brand identification (CBI). Design/methodology/approach: The proposed theoretical model is tested using structural equation modelling approach on the data gathered from 464 consumers. Findings: The paper shows that being more engaged in consumer–brand interactions and perceiving a brand as more humanlike and prestigious increases consumer's identification with product brands. On the other hand, consumer skepticism towards advertising only slightly decreases their identification. CBI is shown to have a strong positive influence on brand loyalty. Research limitations/implications: The study restricts itself to those brands that consumers know well and are somehow close to them. It might prove worthwhile to replicate the study to broaden the inferences beyond the criteria used in this study. Practical implications: To strengthen consumers' identification with their brands, organisations should maintain a focus on interactions with their target consumers. Specifically, companies should expose their human-like character and engage consumers in company's offerings. Also, companies should take care for keeping their competitive edge to be perceived as more prestigious than the competition. Originality/value: While previous papers studying drivers of CBI focused mainly on brand associations that help satisfy one of consumer's self-definitional need, this paper aims to define the drivers of CBI by examining the origins of consumer's interactions with brands. The paper proposes CBE and BA as two vital antecedents of CBI.